The Ontology of Change: Dilemma and Tragedy as Gateways to Deeper Meaning (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
Events that change the course of one's life often appear to occur in flashes – they are not planned or predicted. This paper suggests that such opportunities for change are existent and pervasive in every moment of our life, but for the most part remain undetected until dilemma or tragedy instils an awakening or sharpening of conscious awareness. Nietzsche provides ontology of change, a modicum of philosophical illumination but no experiential detail, nor a coherent application to clinical practice. What is it then that illuminates the landscape of existence to the extent that there is this awakening? This paper is in three parts. Part one explores Nietzsche's philosophy with respect to time. Part two links this with the works of Husserl (2002), Tolle (1999) and Stern (2004), and in the light of parts one and two, some suggestions are made about the implications for therapeutic practice.
Keywords: Consciousness; moment; Nietzsche; presentness; recurrence; silence; Stern; time; Tolle; tragedy.